Efficacy and Realization of Welfare Schemes for Senior Citizens in Kolkata, North (Global Journal of Human-Social Science, 2025)
The steep rise in human life expectancy has resulted in a substantial increase in older people population particularly in the age group of 80 years and above According to the National Policy for Senior Citizens March 2011 the Indian demographic profile shows that in 2000-2050 the population in the age group 60 years to 70 years will increase by 326 and in 80 years above will increase by 700 It has been seen that out of the total World Elderly Population 1 8 of them resides in India The elderly population in India never retires in its strict sense and they continue to work as long as they are physically capable to do As aging is inevitable and physical infirmity entrails age this result in steep decline in earning that eventually amounts to poor savings and decline in standard of living It has been observed that most of the senior citizens of India live in destitute therefore old age income security is one of the greatest challenges amongst the senior citizens A lot of aspects of their standard of living have been taken into account by the government of India to ensure their social security namely economic health socioeconomic and shelter to propose adequate social security schemes Likewise the West Bengal Government as well as introduced certain welfare schemes for the ensuring the social security of the senior citizens However it has been observed that the benefits are not being adequately satisfying the needs of the people This paper tries to address the factors that plays a significant role in realizing the benefits assured to the senior citizens under the various welfare schemes dedicated to their welfare and will also try to find out the factors that poses a barrier to access those rights Statistical dataset has been collected corresponding to a questionnaire and analysis is performed based on the dataset collected which can clearly indicate the impact of different independent factors on the awareness of the scheme for senior citizen
Keywords: senior citizens; welfare schemes; social security; statistical analysis; ANOVA; Chi-square test